My journey to Salford - The Degree Apprentice journey - Louise Annesley (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Louise is a Biomedical Science Degree Apprentice. Louise explains her journey involving her return to education, from unexpected opportunities to building confidence and competence to practice as a future biomedical scientist. She describes what her journey as a student has been like thus far.